Clinical Outcomes After Proton Therapy Reirradiation for Recurrent Malignant Glioma: Analysis From the Prospective Proton Collaborative Group Registry - Omer Gal, MD; Stephen Mihalcik, MD; Lia M. Halasz, MD; John H. Chang, MD; C. Jake Wang, MD; J. Isabelle Choi, MD; Charles B. Simone, II, MD; Carlos E. Vargas, MD; Henry K. Tsai, MD; Rupesh Kotecha, MD; Robert H. Press, MD (Advances in Radiation Oncology, 2025)
Purpose: Optimal treatment for recurrent glioma after prior radiation therapy (RT) is not well established. Proton therapy (PT) is increasingly used for reirradiation (ReRT); however, treatment outcomes, toxicities, and prognostic factors for PT-ReRT remain poorly defined. Methods and Materials: The prospective, multi-institutional Proton Collaborative Group registry was queried for patients with malignant glioma who underwent PT-ReRT between July 2011 and December 2023; only patients with at least one follow-up encounter were included. Overall survival (OS) and progression-free survival were assessed using the Kaplan-Meier method, and Cox proportional hazards regression was used for uni- and multivariable analyses (univariable analysis and multivariable analysis). Results: The study cohort included 143 patients, the median follow-up was 11.2 months, and the median time interval (TI) from prior RT (median 58.5 Gy, IQR, 54-60 Gy) to PT-ReRT (median 44.6 Gy, IQR, 39.4-55.9 Gy) was 42.4 months. Median progression-free survival and OS were 8.1 and 11.2 months, respectively. On univariable analysis, improved OS was associated with oligodendroglioma and astrocytoma histology compared to glioblastoma, TI >60 months, Eastern Cooperative Oncology Group performance status 0, and ReRT dose ≥50 Gy. On multivariable analysis, improved OS remained associated only with oligodendroglioma and TI >60 months. Acute and late grade 3 toxicity occurred in 7% and 4%, respectively. Acute grade 3 toxicity was associated with poor performance status. Incidence of radiographic radiation necrosis was 19%. Conclusions: In the largest series of glioma PT-ReRT reported to date, retreatment was well tolerated with variable outcomes based on clinical prognostic factors. Toxicity rates were similar compared to photon-based literature despite a high median ReRT prescription dose.